Respuesta :

Since x is on the right side of the equation, switch the sides so it is on the left side of the equation.Bxt+C=AB⁢x⁢t+C=ASince CC does not contain the variable to solve for, move it to the right side of the equation by subtracting CC from both sides.Bxt=−C+AB⁢x⁢t=-⁢C+ADivide each term by BtB⁢t and simplify.Divide each term in Bxt=−C+AB⁢x⁢t=-⁢C+A by BtB⁢t.BxtBt=CBt+ABtB⁢x⁢tB⁢t=-⁢CB⁢t+AB⁢tSimplify the left side of the equation by cancelling the common factors.Reduce the expression by cancelling the common factors.xtt=CBt+ABtx⁢tt=-⁢CB⁢t+AB⁢tReduce the expression by cancelling the common factors.Cancel the common factor.xtt=CBt+ABtx⁢tt=-⁢CB⁢t+AB⁢tDivide xx by 11 to get xx.x=CBt+ABt
so x is equal to 1
X=(a-c)/(bt) this needs to be 20 characters long
ACCESS MORE